Prioritarianism for Global Health Investments: Identifying the Worst Off. Issue 1 (5th August 2015) - Sharp, Daniel; Millum, Joseph
Abstract: The available resources for global health assistance are far outstripped by need. In the face of such scarcity, many people endorse a principle according to which highest priority should be given to the worst off. However, in order for this prioritarian principle to be useful for allocation decisions, policy‐makers need to know what it means to be badly off. In this article, we outline a conception of disadvantage suitable for identifying the worst off for the purpose of making health resource allocation decisions. According to our total advantage view: (1) the worst off are those who have the greatest total lifetime disadvantage; (2) advantage foregone due to premature death should be treated in the same way as other ways of being disadvantaged at a time; (3) how badly off someone is depends on the actual outcomes that will befall her without intervention, not her prospects at a time; and (4) all significant forms of disadvantage count for determining who is worst off, not just disadvantage relating to health. We conclude by noting two important implications of the total advantage view: first, that those who die young are among the globally worst off, and second, that the epidemiological shift in the global burden of disease from communicable to non‐communicable diseases should not lead to a corresponding shift in global health spending priorities.